KOMPOSISI DAN STRUKTUR KOMUNITAS PLANKTON SEBAGAI BIOINDIKATOR KUALITAS PERAIRAN SUNGAI INDRAGIRI UNTUK RANCANGAN MEDIA POSTER PADA PEMBELAJARAN BIOLOGI SMA KELAS X - Ahmad Syahwanda; Suwondo Suwondo; Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:This study aims to be used as a source of information about the composition and structure of the palnton community as a bio-indicator of water quality in the Indragiri River. The study was conducted in the Indragiri River, Kuantan Singingi Regency from May to June 2019. The parameters measured were biological parameters and physical chemical parameters of the waters. This research is a descriptive study consisting of research stagein the field and poster design stage. The study was conducted in 5 stations with a purpose random sampling technique, while data collection was carried out using a survey method. The method in this study consists of 2 stages, In the study of Media Poster design using the Addie model which consists of five stages, namely Analysis, design, development, implementation, and evaluation. The data obtained were analyzed descriptively. The results of this study indicate that the composition of phytoplankton in theIndragiri River was found in 5 classes, 23 species and 333 individuals. While the zooplankton composition in the Indragiri River found 5 classes, 8 species and 35 individuals. The highest phytoplankton composition was Closterium kuetzingii with a proportion of 8.11% and the highest zooplankton composition was Nebelia cartosi at 28.57%. The highest abundance of plankton was found at station I, the highest index of plankton species richness was found in stations I and III, the highest plankton evenness indexwas found in stations I and V, the highest plankton diversity index was found at station I. While the plankton dominance index at all stations was low or close zero.Key Words: Fitoplankton, Zooplankton, Kualitas Perairan